PET-HEALTH AND THE DEMOCRATIZATION OF THE DEBATE ON EQUITY: AN EXPERIENCE REPORT - Lucena , Ana Paula Barbosa Nascimento; Barros , Ellen Santos; Silva , Iago Ribeiro Souza; Ribas , Rafaella da Silva Pires; Barbosa , Sarah Regina Santos; Costa , Saulo Evangelista; da Cruz, Rayane Rodrigues; Ribeiro , Juliana Santana; de Andrade , Soraya Sampaio; Santos , Rodrigo Fernandes; de Assunção , Paula Lisiane; Souza , Tuany Santos; et al. (Seven Editora, 2025)
This study aims to describe the experiences of scholarship holders of the Education through Work for Health Program (PET-Saúde), focusing on the process of introduction to the project and the activities developed for the valorization of workers and future workers of the Unified Health System (SUS). This is a descriptive experience report on the experiences in the field in the process of continuing education of health workers. The methodology was established, in part, by the general group of the program, stipulating the places of intervention, the products to be worked on, namely the equity game and the information folder. Group five established a four-stage schedule: welcome and presentation, game, conversation circle, and farewell. During this journey, we encountered a new and challenging topic, involving discussions about gender equity, gender identity, sexuality, race, ethnicity, and disabilities. The initial fear of participating was overcome throughout the meetings, realizing that we were in an environment conducive to collective learning, free of judgment. The exchanges and debates not only broadened technical knowledge but also fostered significant personal growth, teaching us to value diversity and listen with empathy. DOI: https://doi.org/10.56238/sevened2025.002-005